(untitled) (ModaPalavra e-periódico, 2022)
This article approaches the traditional knowledge of Cariri, from Ceará, connecting teaching, design and handicraft, based on the experience developed between the Universidade Federal do Cariri and the artisans of Associação Mãe das Dores, a partnership that aims to relate different knowledges, creating ergonomically comfortable products and utilizing material with environmental responsibility. Through collaborative design, the intention is to create bags that can contribute to the sustainability of communities. The method used is based on problems solving from a demand of artisans and solved with briefing, research, planning and development of the design project, with a multidisciplinary approach involving empirical knowledge of artisans in the creation of braids, through design projects targeted to the market. This research provided the realization of creative manual practices developed in backyard workshops for the creation of embroidery, crochet and hand painting, carried out by students together with artisans, with a focus on personal development.